Head-to-head comparison of 11C-PiB and 18F-FC119S for Aβ imaging in healthy subjects, mild cognitive impairment patients, and Alzheimer's disease patients. Issue 12 (March 2017) - Byun, Byung Hyun; Kim, Byung Il; Park, Su Yeon; Ko, In Ok; Lee, Kyo Chul; Kim, Kyeong Min; Kim, Yu Kyeong; Lee, Jun-Young; Bu, Seon Hee; Kim, Jung Hwa; Chi, Dae Yoon; Ha, Jeong Ho; et al.
Abstract : Abstract: As a new beta amyloid (Aβ) positron emission tomography (PET) tracer, 18 F-FC119S has shown higher cortical uptake in patients with Alzheimer's disease (AD) than that in healthy control subjects without adverse effects in a previous preliminary study. The aim of this study was to compare 18 F-FC119S PET and 11 C-PiB PET in healthy control (HC) subjects, mild cognitive impairment (MCI) patients, and AD patients. A total of 48 subjects, including 28 HC subjects, 10 MCI patients, and 10 AD patients, underwent static 18 F-FC119S PET (30 minutes after intravenous [i.v.] injection) and 11 C-PiB PET (40 minutes after i.v. injection) on the same day. Both PET images were visually and quantitatively assessed. Standardized uptake value ratios (SUVRs) were calculated for each brain region using the cerebellar cortex as a reference region. None (0%) of the 28 HC subjects and 4 (40%) of 10 MCI patients had positive scans on both PET images. Of the 10 AD patients, 7 (70%) had positive scans on 11 C-PiB PET while 6 (60%) had positive scans on 18 F-FC119S PET. Overall, 47 (98%) of 48 participants showed identical results based on visual analysis. Cortical SUVR of 18 F-FC119S was higher in AD patients (1.38 ± 0.16), followed by that in MCI patients (1.24 ± 0.10) and in HC subjects (1.14 ± 0.05). Compared with 11 C-PiB PET, 18 F-FC119S PET yielded a higher effect size ( d = 2.02 vs. 1.67) in AD patients and a slightly lower effect size ( d = 1.26 vs. 1.38) in MCI patients. In HC subjects, the nonspecific binding of 18 F-FC119S to white matter (with the frontal cortex-to-white matter SUV ratio of 0.76) was slightly lower than that of 11 C-PiB (ratio of 0.73). There was a significant linear correlation (slope = 0.41, r = 0.78, P < 0.001) between 11 C-PiB and 18 F-FC119S cortical SUVR. We could safely obtain images similar to 11 C-PiB PET imaging Aβ in the brain using 18 F-FC119S PET. Therefore, 18 F-FC119S might be suitable for imaging Aβ deposition.